Educational Management in Buya Hamka's View - Rakhmad Agung Hidayatullah; Amir Reza Kusuma (Penerbit Hellow Pustaka, 2025)
Buya Hamka was a highly productive figure. He not only produced brilliant ideas, but also inspired the creation of other works. He was also a figure who was not only able to leave behind a legacy of teaching, but whose thoughts became the object of study from various perspectives.4 In his work, Buya Hamka presents several works that encompass various educational disciplines and are presented through a religious approach, namely Islam. According to Buya Hamka, education is an effort to shape the character of students. Every human being born into the world is shaped through education to become someone useful to their society, so that they can understand the difference between good and bad.